Effect of oxidative stress and exercise-induced adaptations - Baghaiee B (مجله دانشگاه علوم پزشکی گرگان, 2015)
Free radicals are unstable molecules in reaction with other molecules lead to a variety of injuries and illnesses. However, to prevent the injuries, enzymatic and non-enzymatic antioxidants react with free radical in various forms. Free radicals and antioxidant enzyme acts by various mechanisms, although age, gender and physical activity affects on these reactions. Different responses and adaptation are experienced to oxidative stress among women and men, young, elderly, subjects with physical fitness and untrained subjects. The present article reviewed the effect of oxidative stress due to exercise-induced adaptations.